If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12Z + 2 = 5Z + -19 Reorder the terms: 2 + 12Z = 5Z + -19 Reorder the terms: 2 + 12Z = -19 + 5Z Solving 2 + 12Z = -19 + 5Z Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-5Z' to each side of the equation. 2 + 12Z + -5Z = -19 + 5Z + -5Z Combine like terms: 12Z + -5Z = 7Z 2 + 7Z = -19 + 5Z + -5Z Combine like terms: 5Z + -5Z = 0 2 + 7Z = -19 + 0 2 + 7Z = -19 Add '-2' to each side of the equation. 2 + -2 + 7Z = -19 + -2 Combine like terms: 2 + -2 = 0 0 + 7Z = -19 + -2 7Z = -19 + -2 Combine like terms: -19 + -2 = -21 7Z = -21 Divide each side by '7'. Z = -3 Simplifying Z = -3
| 11x^2-6000x-27500=0 | | 6(x-2)=9(x-3) | | 7.80+.65y=6.80+.90x | | 0=8x^3+34x^2-29x+5 | | 2x^3+x-8=0 | | -90=-38+4x | | (6x^6/y)^-3 | | -90=-38+4 | | 46*49=56x | | Y=2.3-1.8 | | 46*49=x | | -112=-4(7-3n) | | 2(y-5)=-10y | | 13-5=52 | | a^2-56=-a | | (x+y)(b+x)=0 | | 6(2x+5)+8=12x+38 | | -z^2+11=0 | | (6x-3)-(-3x+2)= | | 3(x-2)=-(6-x) | | 1.5x=1.3x+4 | | 1/4(x-8)1/12= | | 13-5x=-5 | | -6x+30+2x-20-4x+30= | | 5x-9+7x=-21 | | 12-3x+4=-2x+7+8x | | -6x+30+2x-20-4x+30x= | | 3/4(x)=23 | | 41+10x=101 | | 3/4(x)=55 | | 3x+9+2x=-36 | | 2/3(x)=55 |